2009
DOI: 10.1590/s0103-84782009000700017
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da matéria orgânica e distribuição do fósforo no solo de lavouras orgânicas de café Conilon

Abstract: The organic management in coffee uses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
(12 reference statements)
3
10
0
5
Order By: Relevance
“…Labile organic P (Pol) predominated over Pil, in all systems and evaluated depths, which was also observed by other authors (Bowman and Cole, 1978b;Guerra et al, 1996;Solomon et al, 2002;Matos et al, 2006;Cunha et al, 2007;Zaia et al, 2008a,b;Partelli et al, 2009). This fact highlights the importance of the organic fraction, especially in deficient soils, like weathered ones where available P is probably related to Po fractions (Guerra et al, 1996;Cunha et al, 2007).…”
Section: Labile Inorganic and Organic P (Pil And Pol)supporting
confidence: 87%
See 2 more Smart Citations
“…Labile organic P (Pol) predominated over Pil, in all systems and evaluated depths, which was also observed by other authors (Bowman and Cole, 1978b;Guerra et al, 1996;Solomon et al, 2002;Matos et al, 2006;Cunha et al, 2007;Zaia et al, 2008a,b;Partelli et al, 2009). This fact highlights the importance of the organic fraction, especially in deficient soils, like weathered ones where available P is probably related to Po fractions (Guerra et al, 1996;Cunha et al, 2007).…”
Section: Labile Inorganic and Organic P (Pil And Pol)supporting
confidence: 87%
“…However, Xavier et al (2009), evaluating the organic fertilization and the use of green manures in different fractions of P in soil in areas under organic agriculture in Ceará, found that the organic P compartment was responsible for over 50 % of the soil Pt in all the evaluated areas, indicating that the Po forms play a vital role in P cycling and plant nutrition in sandy soils. Despite the higher contribution of Pit, the Pot percentages found in the present study are significant, as suggested by Partelli et al (2009), who obtained a mean of 43 % Pot in soils cultivated with Conilon coffee under different organic production systems.…”
Section: Inorganic and Organic Total Phosphorus (Pit And Pot)supporting
confidence: 54%
See 1 more Smart Citation
“…Esse excesso provavelmente ocorre devido à não-utilização de um sistema de adubação equilibrada, seja química seja orgânica. Partelli et al (2009) O mesmo pode estar ocorrendo com o potássio no sistema convencional, cujo valor médio é considerado alto, de acordo com Raij et al, 1996. Nota-se que mesmo a menor quantidade observada para o potássio no sistema orgânico, este também é considerado alto, indicando que não há problemas de deficiência desse elemento.…”
Section: íNdices De Percepção Ambientalunclassified
“…The use of the Bowman and Cole (1978) and Bowman (1989) methods for extraction of inorganic (Pi) and organic phosphorus (Po) has been proposed by several authors (PARTELLI et al, 2009;BEUTLER, 2012;DUDA et al, 2013;OLIVEIRA et al, 2014;BEUTLER et al, 2015;BEZERRA et al, 2015). These methods allow the extraction of labile, moderately labile, moderately recalcitrant, and recalcitrant P fractions, using different extractors (NaHCO 3 , NaOH, and H 2 SO 4 ), therefore separating soil P into fractions of different plant availability.…”
Section: Introductionmentioning
confidence: 99%